Uropygial gland microbiota of nearctic−neotropical migrants vary with season and migration distance - Leanne A. Grieves; Gregory B. Gloor (Animal Microbiome)
Abstract Symbiotic microbiota are important drivers of host behaviour, health, and fitness. While most studies focus on humans, model organisms, and domestic or economically important species, research investigating the role of host microbiota in wild populations is rapidly accumulating. Most studies focus on the gut microbiota; however, skin and other glandular microbiota also play an important role in shaping traits that may impact host fitness. The uropygial gland is an important source of chemical cues and harbours diverse microbes that could mediate chemical communication in birds, so determining the factors most important in shaping host microbiota should improve our understanding of microbially-mediated chemical communication. Hypothesizing that temporal, geographic, and taxonomic effects influence host microbiota, we evaluated the effects of season, migration distance, and taxonomy on the uropygial gland microbiota of 18 passerine species from 11 families. By sampling 473 birds at a single stopover location during spring and fall migration and using 16S rRNA sequencing, we demonstrate that season, followed by migration distance, had the strongest influence on uropygial gland microbial community composition. While statistically significant, taxonomic family and species had only weak effects on gland microbiota. Given that temporal effects on gland microbiota were nearly ubiquitous among the species we tested, determining the consequences of and mechanisms driving this seasonal variation are important next steps.